Use of Continuity in solving inequalities: Uso de la Continuidad en la resolución de inecuaciones - Sanabria Brenes, Giovanni (2020)
In general, in a usual Differential Calculus course, it is required to solve a series of inequalities, mainly in applications of the derivative, to determine the monotony or concavity of a function. However, although continuity is studied prior to referral, continuity is rarely used to resolve inequalities. The present work outlines a way to make use of continuity in solving inequalities: the analytical method.